2005
DOI: 10.1128/jb.187.18.6565-6570.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Deletion of the Gene rpoZ , Encoding the ω Subunit of RNA Polymerase, in Mycobacterium smegmatis Results in Fragmentation of the β′ Subunit in the Enzyme Assembly

Abstract: A deletion mutation in the gene rpoZ of Mycobacterium smegmatis causes reduced growth rate and a change in colony morphology. During purification of RNA polymerase from the mutant strain, the ␤ subunit undergoes fragmentation but the fragments remain associated with the enzyme and maintain it in an active state until the whole destabilized assembly breaks down in the final step of purification. Complementation of the mutant strain with an integrated copy of the wild-type rpoZ brings back the wild-type colony m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In this study, we provide clear evidence (in vivo and in vitro assembly) that, in contrast to E. coli, M. tuberculosis core could not be well assembled and almost lost its function in the absence of . In addition, a previous study has shown that deletion of the rpoZ gene in M. smegmatis resulted in proteolytic cleavage of RNAP ␤= subunit and further affected the function of RNAP in vivo (18). All these data indicate that mycobacterial plays more important roles than that of E. coli .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, we provide clear evidence (in vivo and in vitro assembly) that, in contrast to E. coli, M. tuberculosis core could not be well assembled and almost lost its function in the absence of . In addition, a previous study has shown that deletion of the rpoZ gene in M. smegmatis resulted in proteolytic cleavage of RNAP ␤= subunit and further affected the function of RNAP in vivo (18). All these data indicate that mycobacterial plays more important roles than that of E. coli .…”
Section: Discussionmentioning
confidence: 85%
“…First, Mycobacterium leprae, which has lost many genes during the process of reductive evolution, still preserves the subunit (8,17). Second, deletion of rpoZ, a gene encodes the subunit, significantly decreased the growth rate of Mycobacterium smegmatis and resulted in proteolytic cleavage of the RNAP ␤= subunit (18). Third, rpoZ has been predicted to be an essential gene in M. tuberculosis by transposon mutagenesis screening (19,20).…”
mentioning
confidence: 99%
“…An rpo Z mutant [ribonucleic acid (RNA) polymerase accessory protein] exhibited strongly impaired growth in the presence of the stressor and was unable to assimilate butanol as sole carbon source. This is likely due to the role of the RpoZ protein in RNA polymerase stability (Mukherjee et al ., ; Mathew et al ., ) along with potential polar effects on the gene encoding SpoT, which influences the cellular content of ppGpp alarmone (Gentry and Cashel, ). In addition, a single mutant in glutamyl‐Q tRNA (Asp) synthetase ( gluQ , translation) was defective in butanol assimilation and tolerance due to its involvement in general metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we subjected the strain mcdrzco for proteome analysis in the similar way (not shown , presented as a supplementary material). mcdrzco was generated by complimenting rpoZ in mcdrz [30], where rpoZ was integrated back to the genome presumably at a different location from the original. The 2D profile showed similar pattern as that of wild type (with respect to spots 1, 2 and 3).…”
Section: Proteomic Analysis Of the Rpoz-deleted MC 2 155mentioning
confidence: 99%
“…, the smallest subunit, has been shown to be an integral part of the assembly which helps to fold the ␤ subunit and protect it physically [29,30]. We have reported earlier that the rpoZ-deleted mc 2 155 strain (mcdrz) displays various pleiotropic phenotypes like altered colony morphology, minimal sliding motility, defective biofilm formation and inability to produce extracellular matrix [30,31].…”
Section: Introductionmentioning
confidence: 99%